MANAGING CHANGES FOR IMPLEMENTING TQM IN INNOVATION PROCESS - Cosmin DOBRIN (Business Excellence and Management, 2013)
The purpose of this article is to study the application of total quality management in the innovation process. This article describes and evaluates concepts and techniques in the field of quality and innovation and identify and symbiosis between these two philosophies.